Granulometryczny wskaźnik gęstości naturalnej gleb = Granulometric coefficient of natural bulk density of soil - Mieczysław Wojtasik; Dawid Aleksander Szatten (Kazimierz Wielki University, 2015)
Wojtasik Mieczysław, Szatten Dawid. Granulometryczny wskaźnik gęstości naturalnej gleb = Granulometric coefficient of natural bulk density of soil. Journal of Education, Health and Sport. 2015;5(5):76-85. ISSN 2391-8306. DOI 10.5281/zenodo.17444 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A76-85 https://pbn.nauka.gov.pl/works/559147 http://dx.doi.org/10.5281/zenodo.17444 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   Granulometryczny wskaźnik gęstości naturalnej gleb   Granulometric coefficient of natural bulk density of soil   Mieczysław Wojtasik, Dawid Szatten   Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Instytut Geografii, 85-428 Bydgoszcz, ul. Mińska 15   Streszczenie Kluczowym wskaźnikiem fizycznej jakości gleby jest gęstość objętościowa, a zwłaszcza jej najbardziej znacząca wielkość, czyli gęstość naturalna (ρn). Gęstość naturalną w całym przedziale zmian kształtuje w największym stopniu granulometryczny wskaźnik g, wyrażany stosunkiem liczbowym frakcji o średnicy 0,5 - 0,1 mm do frakcji o średnicy poniżej 0,002 mm, korygowanym w przypadkach dużej zawartości  frakcji ϕ 0,1 - 0,02 mm. Na podstawie wielkości tego wskaźnika można ustalić rząd wielkości gęstości naturalnej (ρn) dla gleb o podobnej charakterystyce uziarnienia oraz w każdym indywidualnym przypadku, czyli warstwie pedonu, dokładną wielkość tej cechy.   Abstract Key indicator of the physical quality of the soil is bulk density, especially its most significant factor - natural bulk density of soil (ρn). Natural bulk density of soil for the whole range is formed in the greatest extent by granulometric index g, expressed in a relationship of fractions of diameter 0,5 - 0,1 mm and fraction of diameter less than 0,002 mm, corrected in the case of a high content of fraction ϕ 0,1 - 0,02 mm. On the basis of the size of this indicator the order of magnitude natural bulk density (ρn) can be determined for soils with a similar grain size and in each individual case, i.e. specified depth of soil profile, exact amount of this characteristic.   Słowa kluczowe: gęstość naturalna gleby, granulometryczny wskaźnik gęstości naturalnej gleby, zróżnicowanie uziarnienia gleb, grupa i podgrupa granulometryczna utworu glebowego. Key words: natural bulk density of soil, granulometric index of natural bulk density of soil, particle size distribution of soils, grain size groups and subgroups of soils.